2023
DOI: 10.1039/d2na00753c
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon enhanced fluorescence from meticulously positioned gold nanoparticles, deposited by ultra sonic spray coating on organic light emitting diodes

Abstract: Enhancement of the spontaneous emission of the fluorophores aided by plasmonic nanoparticles (PNPs) prompted the growth of plasmonic organic light emitting diodes (OLEDs). Together with the spatial dependence of fluorophore...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that nanoparticles with sharp corners and edges cause stronger localized field enhancement [10,11]. Thus, an enhanced EF can significantly increase the excitation rate of fluorescent emitters [12]. However, PNPs suffer from high dissipative and radiative losses.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that nanoparticles with sharp corners and edges cause stronger localized field enhancement [10,11]. Thus, an enhanced EF can significantly increase the excitation rate of fluorescent emitters [12]. However, PNPs suffer from high dissipative and radiative losses.…”
Section: Introductionmentioning
confidence: 99%